Konsentrasi Geografis, Ukuran Perusahaan, Tipe Industri dan Pengungkapan Corporate Social Responsibility - Pitriyani, Ni Wayan; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2021)
This study analyzed the effect of geographic concentration, company size, and industry type on corporate social responsibility disclosure. Corporate social responsibility disclosure is one of the media to show the company's social care to maintain the legitimacy of the community. This research was conducted on companies listed on the Indonesia Stock Exchange from 2016 to 2018. Samples amounted to 46 companies with 138 observations. Data were analyzed by multiple linear regression. Based on the results of the analysis found that geographic concentration and company size have a positive effect, while the type of industry does not affect the disclosure of corporate social responsibility. The results of this study provide empirical evidence relating to the validity of the theory of legitimacy and can be used as a consideration in decision-making for stakeholders . Keywords: CSR Disclosure; Geographic Concentration; Company Size; Industry Type.